2014
DOI: 10.1056/nejmoa1315817
|View full text |Cite|
|
Sign up to set email alerts
|

A Four-Month Gatifloxacin-Containing Regimen for Treating Tuberculosis

Abstract: Noninferiority of the 4-month regimen to the standard regimen with respect to the primary efficacy end point was not shown. (Funded by the Special Program for Research and Training in Tropical Diseases and others; ClinicalTrials.gov number, NCT00216385.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
348
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(363 citation statements)
references
References 17 publications
7
348
0
8
Order By: Relevance
“…In 2014, three trials were reported that relate to treatment shortening based on the substitution of a fluoroquinolone [9][10][11].…”
Section: Early-phase Clinical Studies Of Moxifloxacinmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2014, three trials were reported that relate to treatment shortening based on the substitution of a fluoroquinolone [9][10][11].…”
Section: Early-phase Clinical Studies Of Moxifloxacinmentioning
confidence: 99%
“…[10] and OFLOTUB [11]. Note that moxifloxacin/rifapentine 900 mg was administered twice weekly and moxifloxacin/rifapentine 1200 mg was administered weekly.…”
Section: Remoxtbmentioning
confidence: 99%
See 2 more Smart Citations
“…The disappointing results from all recent Phase III trials of TB drugs [2][3][4][5] clearly demonstrate that a shift in paradigm is needed in TB drug development. Insufficient efficacy is the main cause for failures in clinical drug development [6,7].…”
Section: Shift In the Tb Drug Development Paradigm: Reality Or Fiction?mentioning
confidence: 99%